Short-term longitudinal clinical, biochemical, and quality of life outcomes of medical or surgical therapy in unilateral primary aldosteronism - Yoshida, Yuichi; Sada, Kentaro; Matsuo, Yoshiro; Nagai, Satoshi; Matsuda, Naoki; Noguchi, Takaaki; Yonezu, Chiaki; Imaishi, Nao; Morita, Machiko; Mori, Yumi; Miyamoto, Shotaro; Ozeki, Yoshinori; et al. (Frontiers in Endocrinology, 2025)
ContextUnilateral primary aldosteronism (uPA) is a surgically curable form of hypertension, frequently associated with resistant hypertension and cerebro-cardiovascular complications. Primary aldosteronism (PA) also negatively affects quality of life (QOL).ObjectiveThis study sought to compare the efficacy of mineralocorticoid receptor antagonists (MRAs) and adrenalectomy (ADX) in the treatment of patients with uPA over time within the same patients and to evaluate the efficacy of MRAs in patients with bilateral PA (bPA).MethodsSubtype diagnosis of PA was based on adrenal vein sampling results. Clinical parameters, including blood pressure, serum potassium (K), active renin concentration (ARC), aldosterone levels, estimated glomerular filtration rate, and Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) scores, were investigated before and after MRA treatment in all PA patients, as well as after ADX in patients with uPA.ResultsThe study included 56 patients with bPA and 20 patients with uPA. Changes in parameters with MRA treatment were similar between patients with and without uPA, except for a greater increase in K in patients with uPA. Among patients with uPA, systolic blood pressure and K improved with MRA treatment and showed further improvement following ADX. Diastolic blood pressure and ARC also improved following MRA treatment, with no significant differences observed compared to ADX. SF-36 scores showed no improvement with MRA treatment, but significantly improved after ADX.ConclusionThe findings showed that ADX generally provides superior clinical, biochemical, and QOL outcomes compared to MRAs in patients with uPA.